Pharmacokinetics of ketoprofen enantiomers following intravenous and oral administration to exercised Thoroughbred horses. (January 2016) - Knych, Heather K.; Arthur, Rick M.; Steinmetz, Stacy; McKemie, Dan S.
Highlights: The pharmacokinetics and bioavailability of two formulations of ketoprofen following oral administration were investigated. Serum concentration time for detection time recommendations is given. Oral F of the injectable formulation were 69.5 ± 10.3% and 88.2 ± 15.9% for R(−) KTP and S(+) KTP. Oral F of the compounded paste formulation were 53.0 ± 6.0% and 53.0 ± 16.0% for R(−) KTP and S(+) KTP. Abstract: Ketoprofen (KTP) is currently only available as an injectable formulation for intravenous administration to horses. The primary goal of the study reported here was to characterize the pharmacokinetics of KTP, including determination of bioavailability following oral administration of the currently available injectable formulation as well as a paste formulation. KTP was administered intravenously and orally, and blood and urine samples were collected at various time points up to 96 h. KTP enantiomer concentrations were determined using LC–MS/MS, and pharmacokinetic analyses were performed. Mean ± standard error values for systemic clearance, steady state volume of distribution and terminal elimination half-life were 0.345 ± 0.033 [R(−) KTP] and 0.167 ± 0.016 [S(+) KTP] L/kg/h, 0.344 ± 0.044 [R(−) KTP] and 0.298 ± 0.025 [S(+) KTP] L/kg, and 2.49 ± 0.077 [R(−) KTP] and 2.86 ± 0.102 [S(+) KTP] h, respectively. Oral bioavailability was calculated as 69.5 ± 10.3% and 88.2 ± 15.9% for R(−) KTP and S(+) KTP, respectively, following administration of the injectable formulation and 53.0 ± 6.0 and 53.0 ± 16.0% for the R(−) KTP and S(+) KTP, respectively, following administration of KTP paste.